PEMERIKSAAN GULA DARAH UNTUK MENCEGAH PENINGKATAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS - Elisa Oktaviana; Bahjatun Nadrati; Lalu Dedy Supriyatna; Zuliardi Zuliardi (Jurnal LENTERA, 2022)
LENTERA (Jurnal PengabdianISSN 2774-812X (print); ISSN 2774-9274 (online)Vol. 2 No. 2 Juli Tahun 2022 pp. 232-237233 | LENTERA (Jurnal pengabdian)ABSTRACTDiabetes mellitus (DM) is a disease, where the condition of glucose levels in the blood exceedsnormal limits. This is because the body cannot release or use insulin adequately. Insulin isa hormone released by the pancreas and is the main substance responsible formaintaining blood sugar levels in the body in a balanced condition. An increase in bloodglucose levels is a common symptom that occurs in people with diabetes mellitus. If leftunchecked, it can cause various complications, both acute and chronic. The purpose ofthis community service is to determine the sugar levels of people with DiabetesMellitus.The method applied in community service activities is the examination of bloodsugar levels in the community by taking blood specimens. The results obtained from 30people with diabetes mellitus that most of the respondents had Blood Sugar Levels <200mg/dL as many as 3 people (10%) and 200 mg/dL 27 people (90%). Patients withDiabetes Mellitus were very enthusiastic about participating in the activity of conductingfree blood level checks, and posyandu cadres were very active during the activity,especially when preparing for implementation so that the measurement activities ransmoothly.It is advisable to check blood sugar levels when carried out on an ongoingbasis to prevent non-communicable diseases as early as possible, especially for peoplewho have the potential to experience the disease and people who already have DiabetesMellitus can control their blood sugar levels so that they remain within reasonable limitsso that signs and symptoms do not occur unwanted symptoms.